Synthesis and evaluation of green magnetic mesoporous molecularly imprinted polymers for adsorption removal of parabens from cosmetic samples - Ramin, Nursyahera Azreen; Asman, Saliza (2023)
Parabens are chemicals that are frequently used as preservatives in numerous cosmetic products. In recent years, the safety concern over these compounds has grown due to their endocrinedisrupting activity. In this research, a novel green magnetic molecularly imprinted polymer (GMMIP) was synthesised using propylparaben as a template and then applied as an adsorbent to selectively recognise and remove parabens from cosmetic samples. The green strategies were introduced by using Persicaria odorata or Kesum leaf extract as a reducing agent to synthesise green magnetic nanoparticles (MNP) as a magnetic core, and deep eutectic solvent (DES) has been designed as an environmentally friendly functional monomer that was used in the preparation of GMMIP. The GMMIP was characterised using Fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscopy (FESEM), and BrunauerEmmett-Teller (BET). The results of FESEM and BET indicated that the GMMIP exhibited an irregular spherical shape and mesoporous characteristics with a pore size of 17.74 nm. The adsorption pH, kinetics, isotherms, and thermodynamics parameters were performed to investigate the interactions that take place between GMMIP and propylparaben. The adsorption processes appeared to best fit the pseudo-second-order kinetic and Freundlich isotherm models at an optimum pH of 12. Findings from a thermodynamics study revealed the adsorption process was exothermic, spontaneous, and more favourable at 298 K. The optimised GMMIP was applied as an adsorbent to remove the parabens from cosmetic samples. When compared to methylparaben and ethylparaben, the GMMIP had the highest selectivity and effectively removed propylparaben, with recoveries ranging from 75.6% to 113.3%. It was found that the limits of detection (LOD) and quantification (LOQ) were between 0.03 and 0.05 mg/L and 0.11 and 0.16 mg/L, respectively. The synthesised GMMIP proved to be a convenient and effective adsorbent to remove parabens from cosmetic products. © 2023